German Family Names in Zagreb and its Suburb: Historical Traces and (Un)changed Identity - Ščukanec, Aleksandra (2008)
For many centuries, the Croatian language has been significantly influenced by German. Croatian-German contacts date back to the first centuries of our era. Apart from the geographical position and various extralinguistic factors, a salient reason for continuing interactions is to be found in an eventful history of the area. German-speaking immigrants even participated in establishing first towns in Croatia, once part of the former Austrian-Hungarian Empire. These contacts have gradually led to certain sociolinguistic changes that are still observable in family names representing a token of one's origin. Family names reflect ethno-political, linguistic, religious, cultural and social conditions of the times they can be traced back to. Moreover, it is often pointed out that a family name can be seen as a constituent part of one's identity. This paper will present an analysis of German family names in Zagreb and Zagreb County. The list of surnames was drawn up from the telephone directory. Since there are numerous examples ranging from the family names that retained their original form to those with hardly recognizable origins, the family names will be categorized according to the level of adaptation and frequency. Modeled after Croatian surnames, the majority of family names illustrate some kind of orthographical, phonological or morphological change. The questionnaires filled in by informants that still bear original German family names will elicit certain data on their roots, possible connections to the homeland of their ancestors and give some indications whether, in their view, a family name and identity are always intertwined concepts.
Projekt MZOS
ENG